ANALISIS VARIASI KECEPATAN PENYAYATAN DAN KEDALAMAN PENYAYATAN TERHADAP KEKASARAN PERMUKAAN AL 5050 MENGGUNAKAN MESIN MILLING RICHON TIPE XK-7132A - Mochammad Lutfi Hendrawan; Fajar Satriya Hadi; Basuki Basuki; Mochamad Arif Irfa’i (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the to identify the lowest surface roughness value achieved through these variations. The research instrument used a surface roughness tester with a total of 27 test samples. The research method employed was quantitative descriptive. The results of this study concluded that: The best surface roughness result at a cutting speed of 75 mm/min achieved an average surface roughness value of 0.09 µm. The best outcome at a cutting depth of 0.1 mm achieved an average surface roughness value of 0.11 µm. The optimal surface roughness result at a cutting speed of 75 mm/min combined with a cutting depth of 0.1 mm yielded a surface roughness of 0.06 µm. This is due to the fact that lower variations in cutting speed and depth result in finer surface roughness.